Dose and Recovery Response of Patellofemoral Cartilage Deformations to Running. Issue 12 (9th December 2020) - Heckelman, Lauren N.; Riofrio, Alexie D.; Vinson, Emily N.; Collins, Amber T.; Gwynn, Olivia R.; Utturkar, Gangadhar M.; Goode, Adam P.; Spritzer, Charles E.; DeFrate, Louis E.
Background: Running is a common recreational activity that provides many health benefits. However, it remains unclear how patellofemoral cartilage is affected by varied running distances and how long it takes the cartilage to recover to its baseline state after exercise. Hypothesis: We hypothesized that patellofemoral cartilage thickness would decrease immediately after exercise and return to its baseline thickness by the following morning in asymptomatic male runners. We further hypothesized that we would observe a significant distance-related dose response, with larger compressive strains (defined here as the mean change in cartilage thickness measured immediately after exercise, divided by the pre-exercise cartilage thickness) observed immediately after 10-mile runs compared with 3-mile runs. Study Design: Descriptive laboratory study. Methods: Eight asymptomatic male participants underwent magnetic resonance imaging of their dominant knee before, immediately after, and 24 hours after running 3 and 10 miles at a self-selected pace (on separate visits). Results: Mean patellar cartilage thicknesses measured before exercise and after the 24-hour recovery period were significantly greater than the thicknesses measured immediately after both the 3- and 10-mile runs ( P < .001). This relationship was not observed in trochlear cartilage. Mean patellar cartilage compressive strains were significantly greater after 10-mile runs compared with 3-mile runs (8% vs 5%; P = .01). Conclusion: Patellar cartilage thickness decreased immediately after running and returned to its baseline thickness within 24 hours of running up to 10 miles. Furthermore, patellar cartilage compressive strains were dose-dependent immediately after exercise. Clinical Relevance: These findings provide critical baseline data for understanding patellofemoral cartilage biomechanics in asymptomatic male runners that may be used to optimize exercise protocols and investigations targeting those with running-induced patellofemoral pain.